Is Southeast Asia Falling into a Latin American-Style Middle-Income Trap? - Palma-Penco, J (Routledge, 2024)
Output and productivity growth slowed in Southeast Asia after the 1997 financial crisis. Latin America experienced a more extreme slowdown following their radical 1980s (post-ISI) neoliberal reforms. This paper explores the causes of the “middle-income trap” and asks if Southeast Asia is following Latin America’s footsteps. In non-resource manufacturing the trap typically manifests when countries are priced out of labor-intensive activities but fail to penetrate more technically sophisticated markets. Natural resource exporters experience the trap when their “extractivist” strategies run out of steam and new engines of productivity growth, such as the processing of raw materials fail to materialize. Mainstream growth theory posits that middle-income countries can escape the trap by doubling down on orthodox policies such as more trade and financial liberalization, further deregulation, and investment in human capital. Yet evidence from countries that have evaded the trap does not support these claims; instead, they have formulated national strategies to promote investment in activities with greater long-term productivity growth potential, especially manufactured exports. The capacity to built flexible industrial strategies is also key. Resource-rich middle-income countries must reinvigorate and sustain their productivity growth by reengineering existing “extractivist” strategies to strengthen backward and forward linkages and leverage natural resource-based industrialization. © 2024 The Author(s). Published with license by Taylor & Francis Group, LLC.